Maternal anthropometry and feeding behavior toward preschool children: association with childhood body mass index in an observational study of Chilean families - Corvalán Camila; Galván Marcos; Lera Lydia; Dominguez-Vásquez Patricia; Kain Juliana; Santos José; Uauy Ricardo (BMC, 2009)
Abstract Background A better understanding of the link between eating behavior and maternal feeding practices with childhood and maternal weight status is of great interest. Objective To assess the association between childhood anthropometric measures with mothers' Body Mass Index (BMI) and their feeding practices toward preschool children in Chile. Methods 1029 children (504 boys, 4.3 ± 0.3 years) and their mothers were selected from public nurseries located in low income neighborhoods in Santiago. Mothers' BMI, children's BMI and waist-to-height ratios were registered. Maternal feeding practices towards their children's nutritional habits were measured using an adapted version of the Child Feeding Questionnaire (CFQ). Results We found a direct correlation (p < 0.001) between children's BMI z-score and their mothers' BMI, both in boys (Spearman rho = 0.26) and girls (rho = 0.30). A direct association was also found between children's BMI z-score with scores of the subscale "concern for child's weight" (Spearman rho = 0.26 in boys and rho = 0.37 in girls; p < 0.001) and "food restriction" (rho = 0.19 in boys and rho = 0.27 in girls; p < 0.001). A reverse significant association was found between children's BMI z-score with scores of "pressure to eat" (rho = -0.30 in boys and rho = -0.36 in girls; p < 0.001). Analyses of the combined categories of childhood obesity and/or maternal obesity showed an important influence of children's weight status on CFQ scores. Conclusion Mothers' BMI and children's BMI z-scores are highly correlated. We found significant associations between mothers' behaviour subscales and children's BMI z-score. It is not possible to establish a causal link between mother's CFQ scores and children's nutritional status, given the cross-sectional nature of this study and the bidirectional influences that exist between mothers and their children.